(untitled) (Bangladesh Journal of Medical Science, 2012)
Objective: Drug resistant tuberculosis has long been a common problem prevailing in developing countries including Bangladesh. Present study focused on the rapid identification of live Mycobacterium tuberculosis among treatment failure cases. Materials and Methods: Sputum samples from a total of 100 category-I and category-II treatment failure cases, assumed as multidrug resistant tuberculosis, were studied through fluorescein diacetate (FDA) staining under light emitting diode (LED) fluorescence microscope. Considering culture method as gold standard, we also compared the results of FDA staining with that of auramine O staining. Results: A total of 85% acid-fast bacilli were detected by FDA staining, 82% by auramine O staining and a total of 85% isolates were detected in Lowenstein-Jensen (LJ) culture. The sensitivity of FDA staining (96.47%) was estimated to be slightly higher than that of auramine O staining (91.76%). Moreover,76.47% cases were detected as multidrug resistant tuberculosis (MDR-TB). Conclusion: Taken together, FDA staining method has been proposed to be appropriate for the rapid diagnosis of drug resistant tuberculosis. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12605 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12